2015
DOI: 10.1152/ajpheart.00413.2015
|View full text |Cite
|
Sign up to set email alerts
|

Value and determinants of the mean systemic filling pressure in critically ill patients

Abstract: Mean systemic filling pressure (Pmsf) is a major determinant of venous return. Its value is unknown in critically ill patients (ICU). Our objectives were to report Pmsf in critically ill patients and to look for its clinical determinants, if any. We performed a prospective study in 202 patients who died in the ICU with a central venous and/or arterial catheter. One minute after the heart stopped beating, intravascular pressures were recorded in the supine position after ventilator disconnection. Parameters at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
8
23
0
Order By: Relevance
“…The impact of volume status on the Q PA /RAP in our model of healthy anesthetized pigs was quantitatively moderate. Overall, our values obtained with the balloon occlusion method are in the same range that others have obtained in pigs (53) and dogs (51) using the same method and are also close to the MSFP of patients in intensive care immediately after death, as reported by Vieillard-Baron and coworkers (62). In contrast, the MSFP values obtained with the inspiratory hold method in patients who are postoperative or septic are considerably higher (42,57).…”
Section: H801supporting
confidence: 90%
“…The impact of volume status on the Q PA /RAP in our model of healthy anesthetized pigs was quantitatively moderate. Overall, our values obtained with the balloon occlusion method are in the same range that others have obtained in pigs (53) and dogs (51) using the same method and are also close to the MSFP of patients in intensive care immediately after death, as reported by Vieillard-Baron and coworkers (62). In contrast, the MSFP values obtained with the inspiratory hold method in patients who are postoperative or septic are considerably higher (42,57).…”
Section: H801supporting
confidence: 90%
“…Notwithstanding the complexity of the vascular architecture and of the elastic state of its vascular segments, we see Pmsf as the distending pressure of a single elastic container filled with the blood volume. As observed by Repessé et al (8) in the presence of a vasoactive substance that increases tone in vascular smooth muscle, we certainly expect a higher Pmsf, other things remaining constant, especially total intravascular volume.…”
Section: George L Brengelmannsupporting
confidence: 64%
“…Department of Physiology and Biophysics, University of Washington, Seattle, Washington TO THE EDITORS: In their recent article published in the American Journal of Physiology-Heart and Circulatory Physiology, Repessé et al (8) recently reported on intravascular pressures [mean systemic filling pressure (Pmsf)] recorded shortly after death in patients in intensive care. With a broad dispersion around an average near 12 mmHg, the only clear influence on Pmsf that could be seen was elevation when norepinephrine had been infused before death.…”
Section: George L Brengelmannmentioning
confidence: 99%
See 1 more Smart Citation
“…The constant c has the dimensions of resistance and is determined by patient anthropometrics that scales the equation for patients of different height, weight and age. The normal mean systemic filling pressure is around 7 mmHg in humans but higher in critically ill patients . From Eqn , it is evident that any increase in the P msa , reflecting an increased effective circulating volume, may be variably partitioned between CVP, mean arterial pressure and cardiac output.…”
Section: Methodsmentioning
confidence: 99%